Dielectric properties of thin-film metal/dielectric nanocomposites based on zirconium nitrides - Артур Альбертович Галиуллин; Иван Владимирович Лунев; Амир Илдусович Гумаров; Игорь Витальевич Янилкин (Physics of Complex Systems, 2024)
Zirconium oxynitride films were synthesized by sputtering zirconium nitride with subsequent atmospheric annealing to oxynitride. The resulting films were studied by dielectric spectroscopy. It was shown that the annealing temperature affects the dielectric properties of the film. Atmospheric annealing leads to dispersion of the permittivity and relaxation processes. The nonlinear nature of the temperature dependence of the relaxation time and the difference in the relaxation times are manifestations of the heterogeneous structure of the films and the size effect of the metal/dielectric structure.